Forecasting winter precipitation over north India - 3-7 days ahead - The synoptic approach (MAUSAM, 1964)
A brief review of some important synoptic methods of Medium Range Forecasting is presented  and the line of approach adopted in the present investigation is indicated. An examination of the mean charts for the winter seasons of the six-year period (1956-61) has revealed the large scale pressure systems which have an influence on winter precipitation over north India for periods of 5-days or more. Some of the interesting and useful relations found between pressure pattern and the corresponding precipitation are presented. The influence of the large scale pressure systems on the fast moving daily disturbances is examined.